Integrating User-Centered Design with the Agile Software Development Methodology for a Cultural Heritage Information System - Nurfarahani, Norman Anuar; Mohd Kamal, Othman (2020)
This paper reports on the findings of a user study on the design ideasfor the Sarawak Digital Cultural Heritage Progressive Web App (PWA). Thestudy elucidates the integration of User-Centered Design (UCD) in the Agile software development methodology. Five users were instructed to map their ideas on how they envisioned the application and the features it would have based on a brief description of the system as a one-stop center cultural heritage information for the general public in Sarawak while encouraging conservation and preservation of material culture. The study found that users prefer a simple and pleasing design with an emphasis on visual representation, and a straight forward and intuitive navigation to minimize cognitive load, Further study should explore the effectiveness of the integration of UCD for the Cultural Heritage Information System from the design stage to the evaluation stage.